The prevalence of burnout syndrome among Critical care Nurses at a tertiary hospital in Pahang Malaysia - Mahamud, Norizumie; Mohamed Ludin, Salizar (2019)
Introduction: Recent studies provide an alarming view on the prevalence of burnout that has increased markedly worldview. However, the study on burnout is still limited in Malaysia. Since no such research has been done in Kuantan, Pahang, this study seeks to close the gap regarding the burnout syndrome. Objective: This study is to determine the prevalence and level of burnout among critical care nurses in one tertiary hospital in Pahang, Malaysia. This study also investigated the association between socio-demographic characteristics and burnout levels among critical care nurses and the correlation between burnout element and burnout level. Methods: A cross-sectional study was done to recruit 118 Critical Care nurses using convenient sampling. Maslach Burnout Inventory-Human Services Survey (MBI-HSS) was used to assess emotional exhaustion (EE), depersonalization (DP) and personal accomplishment (PA) among critical care nurses. It consists of 22 items with a 7-point Likert type rating scale. Results: There was no significant difference between socio-demographic characteristics and the levels of burnout. 64.4% of respondents scored high on emotional exhaustion, while most of the respondents (72.9%) had high levels of depersonalization and 37.3% of the respondents reported high levels of personal accomplishment score. Conclusion: Overall, despite of having high levels of emotional exhaustion and depersonalization, critical care nurses in the tertiary hospital can maintain a positive evaluation of their own accomplishment (PA).